TRANSFORMASI MAKNA KEMATIAN DALAM KEPERCAYAAN SUKU NIAS: ANTARA WARISAN BUDAYA DAN KONTEKS KEKRISTENAN - Matheus Mangentang (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
The Nias tribe has a unique view of death reflected in its beliefs and traditions. It reflects a blend of Christian elements with local beliefs rich in myths, rituals, and symbolism. Local beliefs are reflected in traditional ceremonies rich in symbols and meanings. But it has slowly adapted to the changing times. It is undeniable that the people of Nias are facing significant transformations due to globalization and modernization. These changes not only affect the way of life economically and socially but also change the understanding and management of corpse. This study uses literature as a guideline in compiling this article. To obtain data, use a qualitative field or ethnographic approach to the social and culture of the Nias tribe. The results indicate that the meaning of death for the Nias tribe has changed along with the interaction with the influence of globalization and modernization. The tradition of death, rich in spiritual and social values, remains a strong foothold in maintaining its cultural identity, despite its adaptation to contemporary dynamics